From China to Malaysia: understanding the cultural and economic dynamics of imported Chinese films - Wang, Changsong (Penerbit Universiti Kebangsaan Malaysia, 2024)
The connection between China’s diplomatic engagements abroad and its trans-border film trade holds considerable importance. Inherent in this dynamic is cross-cultural interaction and inter-cultural communication. Malaysia’s support for China’s Belt and Road Initiative has fostering a growing cultural exchange, particularly through the trade of Chinese films, some of which have aschieved significant box office earning success in Malaysia. Despite occasional media attention, there is a notable lack of scholarly literature addressing the impact of these films on Malaysian audiences. This study examines the cinematic consumption of the films imported from China by Malaysian distributors for exhibition to its cinemagoers, using Song Hwee Lim’s framework of conceptualization of transnational cinema. It seeks to better understand the phenomenon of the imported Chinese films for audience appeal, cultural influence and impact on box-office earnings. By collecting and analyzing relevant data from distributors through in-depth interviews with their representatives, this study identifies the approaches of film promotion and marketing activities that are reshaping the cultural experience of filmic storytelling in the Malaysian context. The implications of this study extend beyond film distribution, offering insights into how transnational cinema can shape cultural narratives and influence the cultural landscape in a globalized context. By examining the interplay between Chinese films and Malaysian audiences, the research highlights the role of transnational cinema in fostering cultural exchange and understanding, as well as its potential to impact the future direction of filmic storytelling within a multicultural society.